Rewriting Humour in Comic Books Cultural Transfer and Translation of Aristophanic Adaptations - Asimakoulas, Dimitris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book examines comic book adaptations of Aristophanes' plays in order to shed light on how and why humour travels across cultures and time. Forging links between modern languages, translation and the study of comics, it analyses the Greek originals and their English translations and offers a unique, language-led research agenda for cultural flows, and the systematic analysis of textual norms in a multimodal environment. It will appeal to students and scholars of Modern Languages, Translation Studies, Comics Studies, Cultural Studies and Comparative Literature. Dimitris Asimakoulas is a Lecturer in Translation Studies at the University of Surrey, UK. His research focuses on humour, minority identities in literature and film, and translation history. .
Chapter 1: Introduction -- Chapter 2: Rewriting -- Chapter 3: Transition to comic book text. A different mode of engagement -- Chapter 4: Towards a poetics of humour -- Chapter 5: Repeated logic offenders: Comic Characters -- Chapter 6: Concluding Remarks.
Keywords: Translating and interpreting; Comparative literature; Greek language; Linguistics -- Methodology; Germanic languages; Computational linguistics; Language Translation; Comparative Literature; Greek; Research Methods in Language and Linguistics; Germanic Languages; Computational Linguistics